Matter–wave interference and deflection of tripeptides decorated with fluorinated alkyl chains. (4th May 2020) - Schätti, Jonas; Köhler, Valentin; Mayor, Marcel; Fein, Yaakov Y.; Geyer, Philipp; Mairhofer, Lukas; Gerlich, Stefan; Arndt, Markus
Abstract: Studies of neutral biomolecules in the gas phase allow for the study of molecular properties in the absence of solvent and charge effects, thus complementing spectroscopic and analytical methods in solution or in ion traps. Some properties, such as the static electronic susceptibility, are best accessed in experiments that act on the motion of the neutral molecules in an electric field. Here, we screen seven peptides for their thermal stability and electron impact ionizability. We identify two tripeptides as sufficiently volatile and thermostable to be evaporated and interfered in the long‐baseline universal matter‐wave interferometer. Monitoring the deflection of the interferometric molecular nanopattern in a tailored external electric field allows us to measure the static molecular susceptibility of Ala–Trp–Ala and Ala–Ala–Trp bearing fluorinated alkyl chains at C‐ and N‐termini. The respective values are 4 π ε 0 × 330 ± 150 Å 3 and 4 π ε 0 × 270 ± 80 Å 3 .